7+5q-(5q+1)-(2q+7)=

Simple and best practice solution for 7+5q-(5q+1)-(2q+7)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7+5q-(5q+1)-(2q+7)= equation:


Simplifying
7 + 5q + -1(5q + 1) + -1(2q + 7) = 0

Reorder the terms:
7 + 5q + -1(1 + 5q) + -1(2q + 7) = 0
7 + 5q + (1 * -1 + 5q * -1) + -1(2q + 7) = 0
7 + 5q + (-1 + -5q) + -1(2q + 7) = 0

Reorder the terms:
7 + 5q + -1 + -5q + -1(7 + 2q) = 0
7 + 5q + -1 + -5q + (7 * -1 + 2q * -1) = 0
7 + 5q + -1 + -5q + (-7 + -2q) = 0

Reorder the terms:
7 + -1 + -7 + 5q + -5q + -2q = 0

Combine like terms: 7 + -1 = 6
6 + -7 + 5q + -5q + -2q = 0

Combine like terms: 6 + -7 = -1
-1 + 5q + -5q + -2q = 0

Combine like terms: 5q + -5q = 0
-1 + 0 + -2q = 0
-1 + -2q = 0

Solving
-1 + -2q = 0

Solving for variable 'q'.

Move all terms containing q to the left, all other terms to the right.

Add '1' to each side of the equation.
-1 + 1 + -2q = 0 + 1

Combine like terms: -1 + 1 = 0
0 + -2q = 0 + 1
-2q = 0 + 1

Combine like terms: 0 + 1 = 1
-2q = 1

Divide each side by '-2'.
q = -0.5

Simplifying
q = -0.5

See similar equations:

| (x+2)(x-1)+(x+5)(x-3)=-8 | | 5.1x=-15 | | r=15/1.5 | | 29-x=18 | | 4m^2-16=0 | | 11-11a=11 | | 54/45-41/6+58/15 | | 40+35x=60+25x | | 3x-5x-20=-(x-7) | | 40x+35x=60x+25x | | x+160+3x=180 | | 2(x+5)+4x-19=2x+7-(3-x) | | Log(x)-log(x+3)=1 | | 1/2+3/2x+2/3-x/3=5/6 | | -2y^2+4y^3= | | 6x+x^2=55 | | 2x^2-34x=336 | | 6-6c=41 | | 120=(x+3)(x+1) | | 1/4d=12 | | -2(x-3)+10=4(5-4x) | | -5-c=25 | | -9b+3=-24 | | -24+6x=48 | | -4n+14=-2n-12 | | 20x^2+20x+20=0 | | 36=-8b-8 | | 33=-2y+25 | | 40=-6-5w | | 10-x=25 | | 900=120+(30+x) | | 8x-3x=-50 |

Equations solver categories